USING SOFTWARE TOOLS WHEN CREATING ELECTRONIC TEXTBOOKS (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
This article reveals the methods of using software tools when creating electronic textbooks and their application in the educational process